PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA KURIKULUM 2013 DI KELAS XI SMA NEGERI 2 KOTA BENGKULU - Michael Johan Sulistiawan; Didi Yulistio; M. Arifin (Universitas Bengkulu, 2017)
The purpose of this study is to describe the implementation of Indonesian language learning in the class XI SMA Negeri 2 Kota Bengkulu. This research uses qualitative approach with descriptive method. Techniques used in collecting data are observation, document recording, and interview. The results showed that Indonesian teachers of class XI SMA Negeri 2 Kota Bengkulu carry out Indonesian language learning with the steps as in the Curriculum 2013, namely; 1) preliminary activities, 2) core activities, and 3) closing activities. Some suggestions the author wishes to convey are: 1) the teacher should improve the understanding of the Curriculum 2013 by attending seminars, workshops, training on Curriculum 2013 or studying books Curriculum 2013; 2) School parties should regularly conduct training or seminars of Curriculum 2013; 3) for the researcher, there is a need for further research regarding the implementation of learning for schools using the Curriculum 2013.